Novel Bispecific Antibody for Synovial-Specific Target Delivery of Anti-TNF Therapy in Rheumatoid Arthritis - Ferrari, Mathieu; Onuoha, Shimobi C.; Fossati-Jimack, Liliane; Nerviani, Alessandra; Alves, Pedro L.; Pagani, Sara; Deantonio, Cecilia; Colombo, Federico; Santoro, Claudio; Sblattero, Daniele; Pitzalis, Costantino (Frontiers in Immunology, 2021)
Biologic drugs, especially anti-TNF, are considered the gold standard therapy in Rheumatoid arthritis. However, non-uniform efficacy, incidence of infections and high costs are major concerns. Novel tissue-specific agents may overcome current limitations of systemic administration, providing improved potency and safety. We developed a bispecific antibody (BsAb), combining human arthritic joint targeting, via the synovial specific scFv-A7 antibody, and TNFα neutralization, via the scFv-anti-TNFα of Adalimumab, with binding/blocking capacity comparable to Adalimumab-IgG. Tissue targeting capacity of the BsAb was confirmed on human arthritic synovium in vitro and in a synovium xenograft SCID mouse model. Peak graft accumulation occurred at 48h post-injection with sustained levels over Adalimumab-Ig for 7 days, and increased therapeutic effect, efficiently decreasing tissue cellularity and markers of inflammation with higher potency compared to standard treatment. This study provides the first description of a BsAb capable of drug delivery specifically to the disease tissue and strong evidence of improved therapeutic effect on human arthritic synovium, with applications to other existing biologics.